2019
DOI: 10.1016/j.heliyon.2019.e01802
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for email spam filtering: review, approaches and open research problems

Abstract: The upsurge in the volume of unwanted emails called spam has created an intense need for the development of more dependable and robust antispam filters. Machine learning methods of recent are being used to successfully detect and filter spam emails. We present a systematic review of some of the popular machine learning based email spam filtering approaches. Our review covers survey of the important concepts, attempts, efficiency, and the research trend in spam filtering. The preliminary discussion in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
201
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(203 citation statements)
references
References 59 publications
0
201
0
2
Order By: Relevance
“…Dada et al [129] examined the applications of ML techniques to the email spam filtering process of leading internet service providers (ISPs), such as Gmail, Yahoo, and Outlook, and focused on revisiting the machine learning techniques used for filtering email spam over the 2004-2018 period, such as K-NN, NB, Neural Networks (NN), Rough set, SVM, NBTree classifiers, firefly algorithm (FA), C4.5/J48 decision tree algorithms, logistic model tree induction (LMT), and convolutional neural network (CNN). Stochastic optimization techniques, such as evolutionary algorithms (EAs), have also been explored by Dada et al [129], as the optimization engines are able to enhance feature selection strategies within the anti-spam methods, such as the genetic algorithm (GA), particle swarm optimization (PSO), and ant colony algorithm (ACO).…”
Section: Email Miningmentioning
confidence: 99%
“…Dada et al [129] examined the applications of ML techniques to the email spam filtering process of leading internet service providers (ISPs), such as Gmail, Yahoo, and Outlook, and focused on revisiting the machine learning techniques used for filtering email spam over the 2004-2018 period, such as K-NN, NB, Neural Networks (NN), Rough set, SVM, NBTree classifiers, firefly algorithm (FA), C4.5/J48 decision tree algorithms, logistic model tree induction (LMT), and convolutional neural network (CNN). Stochastic optimization techniques, such as evolutionary algorithms (EAs), have also been explored by Dada et al [129], as the optimization engines are able to enhance feature selection strategies within the anti-spam methods, such as the genetic algorithm (GA), particle swarm optimization (PSO), and ant colony algorithm (ACO).…”
Section: Email Miningmentioning
confidence: 99%
“…The header is created (14) by combining the destination (15) and initial header information (16) to fill the IP address fields.…”
Section: )mentioning
confidence: 99%
“…The work in [9] by Dada et al [10] concluded that there is a need to apply deep learning to spam filtering in order to exploit its numerous processing layers and many levels of abstraction to learn representations of data. The work in discusses the importance of traffic prediction in order to eliminate traffic redundancy in the cloud.…”
Section: Related Workmentioning
confidence: 99%